The Relationship Between Speaking Skills and Psycholinguistics - Xamidullayeva , Fotima Adxam qizi (The Lingua Spectrum, 2026)
This article analyzes the complexity of speaking skills in the process of language learning from a psycholinguistic perspective. The main psycholinguistic processes that explain the formation of speech in teaching Uzbek as a foreign language - speech planning, coding, articulation, monitoring, automation, etc. – are highlighted based on scientific sources. Based on the research of leading scientists such as Bygate, Levelt, Goh and Burns, Richards and Newton, the complexity of the process of oral speech and the psychological and cognitive factors that affect the methodology of teaching it are highlighted.